2019
DOI: 10.7567/1882-0786/ab5bf7
|View full text |Cite
|
Sign up to set email alerts
|

Role of surface defects in the efficiency degradation of GaInN-based green LEDs

Abstract: The role and effect of surface defects (SDs) on the efficiency degradation of GaInN-based green LEDs was investigated. Two types of green LED samples having the same structure were prepared; an additional underlying layer was introduced in one sample to artificially reduce SDs in the multiple quantum well active region. Then, various characteristics were analyzed for both samples. Based on these analyses, schematic models including those of SD dynamics during growth and potential fluctuation induced by SDs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…39−42 Importantly, they are adopted in the simultaneous evaluation of the DW and apparent doping level; the distribution/profile of the carrier density across the MQW can be estimated quantitatively. 22,42 From this viewpoint, in this section, we attempt to investigate and analyze the effect of the pre-TMIn flow treatment of QWs on the distribution of defects in the MQWs by measuring C−V curves. For the measurement, we fabricated the devices using LEDs 0−5 with the lateral electrodes and the size of 300 × 300 μm 2 after the growth of an Mg-doped p-type GaN layer and p + contact layer on the top of MQWs.…”
Section: Acs Applied Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…39−42 Importantly, they are adopted in the simultaneous evaluation of the DW and apparent doping level; the distribution/profile of the carrier density across the MQW can be estimated quantitatively. 22,42 From this viewpoint, in this section, we attempt to investigate and analyze the effect of the pre-TMIn flow treatment of QWs on the distribution of defects in the MQWs by measuring C−V curves. For the measurement, we fabricated the devices using LEDs 0−5 with the lateral electrodes and the size of 300 × 300 μm 2 after the growth of an Mg-doped p-type GaN layer and p + contact layer on the top of MQWs.…”
Section: Acs Applied Materialsmentioning
confidence: 99%
“…16−21 Our recent studies showed that the SDs in an n-type GaN are most likely nitrogen vacancies (V N ), divacancies comprising Ga and N vacancies (V Ga V N ), and/or a V N impurity complex, which are intensively distributed within about 100 nm from the growth surface of n-type GaN. 16,22 Note that the SDs are easily incorporated with In atoms owing to strong affinity between them; therefore, an introduction of a GaInN or AlInN layer between the n-type GaN and the MQWs [i.e., an underlying layer (UL)] is very useful to improve the IQE by trapping the SDs therein. 22,23 However, a further increase in the In content and/or thickness of the UL to enhance the SD trapping frequently has negative impacts on the device performance because it generates threading dislocations (TDs) and absorbs the photons emitted from the MQWs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the result in Fig. 10, the power efficiency (PE, (8) www.nature.com/scientificreports/ η PE and η PE = η EQE × η VE ) 48 in low current regime is expected to enhance even above 100% thanks to the additional energy supplying to carrier 13,43 . From the experimental results and considerations discussed above, we can conclude as follows: (i) the SRH recombination increases with temperature, which well matches to theoretical prediction; (ii) the carriers in MQWs are energized by extrinsic factors, most likely by the SRH recombination and the lattice vibration, which is enhanced with elevated temperature; (iii) when the carriers gain sufficient energy to overcome the band offset from the extrinsic factors, the carrier escaping outside the MQWs is accelerated; (iv) the energized carriers induce the further reduction of radiative recombination probability; and (v) the reduction of IE and B accelerate the thermal droop.…”
Section: Thermodynamic Analysis Of Ledsmentioning
confidence: 99%
“…Particularly, GaInN-based blue LEDs covered with yellow phosphors are being used widely as general white-light sources 6 , 7 . Despite the recent significant progress, however, AlGaInN-based LEDs still suffer from several efficiency degradations, such as the external quantum efficiency (EQE, η EQE ) gradually degrading with increasing emission wavelength, driving current, and operating temperature, often referred to as “green-gap,” “efficiency droop,” and “thermal droop,” respectively 8 10 . Specifically, the thermal droop in GaInN-based blue LEDs has recently become a major research topic because of the continuous demand on white-light emitters that work efficiently in any operating environment 10 14 .…”
Section: Introductionmentioning
confidence: 99%